2019
DOI: 10.1002/ppul.24580
|View full text |Cite
|
Sign up to set email alerts
|

Small for gestational age birth may increase airflow limitation in bronchopulmonary dysplasia

Abstract: Objectives To determine significant indices for assessing the pulmonary function of infants according to bronchopulmonary dysplasia (BPD) severity and to evaluate whether small for gestational age (SGA) could affect pulmonary function in BPD. Methods We evaluated 117 preterm infants who had undergone tidal breathing flow‐volume loop and multiple‐breath washout analyses within 7 months after birth. We categorized preterm infants according to BPD severity into mild/moderate BPD (n = 86), severe BPD (n = 21), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…However, in the subgroup analysis, mechanical ventilation lost its effect on tPTEF/tE for infants with BW > 1000 g who had a median MV duration of one day, while infants with BW < 1000 g presented a trend to worse tPTEF/tE, without reaching statistical significance, probably due to the relative small sample size. In line with our results, a recent study on preterm infants pulmonary function testing with BPD identified a correlation between tPTEF/tE and mechanical ventilation duration and reported a lower value of this obstructive parameter from infants SGA 36 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the subgroup analysis, mechanical ventilation lost its effect on tPTEF/tE for infants with BW > 1000 g who had a median MV duration of one day, while infants with BW < 1000 g presented a trend to worse tPTEF/tE, without reaching statistical significance, probably due to the relative small sample size. In line with our results, a recent study on preterm infants pulmonary function testing with BPD identified a correlation between tPTEF/tE and mechanical ventilation duration and reported a lower value of this obstructive parameter from infants SGA 36 …”
Section: Discussionsupporting
confidence: 93%
“…In line with our results, a recent study on preterm infants pulmonary function testing with BPD identified a correlation between tPTEF/tE and mechanical ventilation duration and reported a lower value of this obstructive parameter from infants SGA. 36 Being SGA have an impact on structural lung and airways immaturity. Specifically, prenatal growth restriction has a detrimental effect on small airways maturation and reduces the number of alveoli at birth which can persist over time with a limited possibility of catchup growth.…”
Section: T a B L E 3 General Linear Model In Overall Populationmentioning
confidence: 99%
“…This nding is partially consistent with the results of Jackson et al, 20 who suggested asthma diagnosis in children born before 28 weeks gestation is predominantly associated with post-NICU risk factors, especially low socioeconomic status, but not with neonatal complications, including BPD. Kim et al 21 reported that small for gestational age infants were associated with poor pulmonary function showing obstructive patterns within BPD patients within the rst year of life. Therefore, the in uence of BPD on asthma may be diminished when the population is limited to extremely preterm or VLBW infants because birth weight and prematurity are relatively predominant risk factors for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…32 Although there have been studies comparing lung function between infants with BPD and those without this diagnosis, there are limited data in preterm infants who are born small for gestational age (SGA). (YH) Kim et al 33 investigated the differences in airway obstruction in term, healthy neonates and preterm neonates with and without BPD using MBW and TBA. No significant differences in the ratio of the time to peak expiratory flow over total expiratory time (Tpef/Te) were observed between the term infants, preterm infants with mild/ moderate BPD, and preterm infants with severe BPD.…”
Section: Physiologic Outcomes Of Prematuritymentioning
confidence: 99%